Sistem Pemerintahan di Kesultanan Ternate - Humah, Darsis; Arifin, Zainuddin; Wajo, Abd. Rauf (Jurnal Ilmiah Wahana Pendidikan, 2024)
This study analyzes the governance system of the Sultanate of Ternate from the perspective of Siyasah Dusturiyah, an Islamic constitutional law concept emphasizing justice, deliberation (shura), and legitimate leadership. As one of the oldest Islamic sultanates in the Nusantara, the Sultanate of Ternate has a governance structure that integrates Islamic law with local customs. The objective of this study is to examine how the principles of Siyasah Dusturiyah are implemented in the governance system of the Sultanate of Ternate and their relevance in the context of modern Islamic constitutional law.This research employs a qualitative approach with a descriptive analysis method, utilizing historical documents, Islamic legal literature, and relevant academic references. The findings indicate that the Sultanate of Ternate continues to uphold several key principles of Siyasah Dusturiyah, including shura (deliberation), wilayah al-amr (the ruler’s authority in policy-making based on Sharia), and the role of Mahkamah Syar’iyyah in the Islamic judicial system. Additionally, the Bobato Nyagimoi se Tufkange (Sultanate Advisory Council) functions as a supervisory body for the Sultan’s policies, reflecting the ahl al-hall wa al-‘aqd principle in Islamic political theory. Despite adaptations due to modernization and state intervention, the governance system maintains Islamic values in decision-making. This study affirms that the principles of Siyasah Dusturiyah remain relevant in modern governance and can be integrated into Indonesia’s national legal system, particularly in aspects of justice, deliberation, and leadership oriented toward public welfare